2019
DOI: 10.1111/chd.12817
|View full text |Cite
|
Sign up to set email alerts
|

Three year experience of a clinical cardiovascular genetics program for infants with congenital heart disease

Abstract: Objective To describe the first 3 years of experience of having an inpatient “cardiogenetics” program which involves medical geneticist assessment of infants with major congenital heart disease (CHD) requiring surgical intervention in the first year of life. Patients Patients less than a year of age admitted to Children's Hospital of Wisconsin's Herma Heart Institute for surgical intervention for CHD seen by the cardiogenetics program. Patients with major trisomies (13, 18, and 21) were excluded. Outcome Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
(35 reference statements)
1
7
2
Order By: Relevance
“…They emphasize that the involvement of a geneticist is critical [28]. The other studies of postnatal cohorts all reported higher yields than the 12% found in our study, with rates of 17% [37], 27% [39], and 36% [20]. In all of these studies, molecular testing was sent as second tier based on a geneticist's evaluation.…”
Section: Incorporation Of Evaluation By Medical Geneticist Increases Syndrome Diagnosis and Molecular Genetic Testing Is Additivecontrasting
confidence: 40%
See 4 more Smart Citations
“…They emphasize that the involvement of a geneticist is critical [28]. The other studies of postnatal cohorts all reported higher yields than the 12% found in our study, with rates of 17% [37], 27% [39], and 36% [20]. In all of these studies, molecular testing was sent as second tier based on a geneticist's evaluation.…”
Section: Incorporation Of Evaluation By Medical Geneticist Increases Syndrome Diagnosis and Molecular Genetic Testing Is Additivecontrasting
confidence: 40%
“…Some of the CHD infants who were not tested can be attributed to logistical issues related to test ordering and the realities of inpatient intensive care unit workflows. In addition to the current study, there have been two recent studies in infants with critical CHDs utilizing a comprehensive clinical algorithm for genetic testing with CMA [20,39]. In the study by Geddes et al, 98% of inpatient CHD infants underwent evaluation by a geneticist and genetic testing [20], whereas in the study by Skikany et al [39] and the current study, approximately 85-90% of patients underwent genetic testing.…”
Section: Redundant Genetic Testing Occurs Frequently Without a Clinical Algorithmmentioning
confidence: 67%
See 3 more Smart Citations